Sosialisasi Wisata Edukasi Bagas Godang Pijorkoling Terintegrasi Dengan Biologi - Siregar, Ali Padang; Kasmawati; Tambunan, Elissa Evawani; Mahrani; Ahmad Rafii; Hsb, Putri Nadya (Jurnal Pengabdian kepada Masyarakat Radisi, 2024)
Educational tourism is tourism related to learning. One of the tours used is Bagas Godang Pijorkoling. The lack of promotion in this case has caused Bagas Godang Pijorkoling to be less well known to the public. The method used is using situation analysis related to observations made on objects, preparation, namely using interview instruments which will later be used during implementation, carrying out socialization about educational tourism and evaluation to see participant responses. The results obtained were that the Bagas Godang socialization activity provided a positive response to the socialization participants so that this socialization was said to be successful. This socialization participant also hopes that with this activity it will be realized that Bagas Godang will be used as an educational tourist attraction in Padangsidimpuan City to improve the standard of living of the surrounding community